THE ROLE OF CULTURAL COMPONENT IN ENGLISH LANGUAGE TEACHING - Akhmedova Matlubakhon Ibragimjonovna; Mukhtorova Rakhimaxon Vokhidjon qizi (Innovate Conferences, 2025)
In today’s interconnected world, English language teaching (ELT) demands more than grammar drills and vocabulary lists—it requires the inclusion of cultural understanding. This paper explores the significance of the cultural component in ELT and how its integration strengthens learners’ communicative competence. Culture-based instruction equips students with both linguistic skills and the cultural literacy needed to interpret meaning, apply politeness strategies, and avoid misunderstandings in real-life contexts. Practical methods such as culture capsules, authentic materials, and scenario-based simulations are discussed. Ultimately, cultural competence is presented not as a secondary aspect but as a vital element of successful language acquisition and intercultural communication.
Keywords: English Language Teaching, Cultural Competence, Intercultural Communication, Pragmatic Awareness, Language and Culture Integration, Cultural Literacy, Global Mindedness.